Work-Life Balance as a Pathway to Improve Gig Workers Performance in Indonesia: The Role of Flexible Work Arrangement and Job Autonomy (Study of Transportation Sector in West Java, Central Java, East Java Provinces) - Azhar Humaira Syabani; Anita Silvianita; Alex Winarno (PT FORMOSA CENDEKIA GLOBAL, 2025)
The rapid growth of the gig economy in Indonesia's transportation sector offers workers a high degree of flexibility and autonomy, but it also poses challenges in maintaining a work-life balance, which impacts performance. This study analyzes the influence of Flexible Work Arrangements and Job Autonomy on Gig Worker Performance, with Work-Life Balance as an intermediary variable. Using a quantitative survey approach, data was collected from gig workers in West Java, Central Java, and East Java who met specific criteria. The findings aim to provide insights into how flexible work structures and autonomy influence performance through work-life balance. These findings are expected to contribute to academic discussions and practical policies to enhance the well-being and productivity of gig workers in the digital economy.